OPTIMALISASI SISTEM INFORMASI KESEHATAN DALAM PENGELOLAAN DATA MATERNAL DAN NEONATAL - Yeni Trisna Purba; Arthauly Gracia Sinaga; Putri Handayani Simbolon (Politeknik Ganesha Medan, 2023)
Accurate, complete, and real-time maternal and neonatal data is an essential foundation for policy planning, clinical decision-making, program monitoring, and evaluation of maternal and neonatal health outcomes. Health Information Systems (HIS) have significant potential to transform the way these data are managed, from error-prone manual recording to efficient, integrated systems. This literature review aims to explore strategies for optimizing HIS in maternal and neonatal data management, identifying existing challenges, potential benefits, and best approaches for implementation and maintenance. The review indicates that integrated and user-friendly HIS can improve data quality, reduce duplication, accelerate reporting, support evidence-based decision-making, and facilitate epidemiological surveillance. Key challenges include system interoperability, the digital divide, user resistance, and the need for ongoing training. Optimizing HIS requires political commitment, infrastructure investment, and human resource capacity development.